Penguatan Peran Mahasiswa dalam Ekonomi Kreatif Berbasis Budaya Melalui Pembentukan JAPAN (Jejaring Pemuda Aktif Negeri) di Politeknik Negeri Subang: Penelitian - Tita Nurmalinasari Hidayat; Dwi Wahyu Kartikasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is motivated by the crucial role of students as the younger generation in the development of a culture-based creative economy in Subang Regency. The primary objective of this study is to establish JAPAN (Jejaring Pemuda Aktif Negeri) as a platform to enhance the knowledge, understanding, and awareness of Politeknik Negeri Subang students regarding the creative economy and the preservation of local culture. This study employs a qualitative approach with a descriptive method. The findings indicate that the level of knowledge and awareness among Politeknik Negeri Subang students regarding the creative economy and culture still needs improvement. The formation of JAPAN within Politeknik Negeri Subang is expected to be a strategic solution capable of accommodating students to actively participate in the development of a culture-based creative economy, strengthen regional identity, and encourage the sustainability of creative programs, such as the widely recognized promotion of Wisma Karya. The sustainability of JAPAN is crucial for ensuring that students' roles in Subang's creative economy and culture continue to evolve and deliver tangible impact to the community.